2014
DOI: 10.5588/ijtld.14.0016
|View full text |Cite
|
Sign up to set email alerts
|

Airflow obstruction among street vendors who refill cigarette lighters with liquefied petroleum gas

Abstract: Likely heavy exposure to LPG through manually refilling cigarette lighters is associated with airflow decrements. This adverse effect may be relevant to other occupational groups heavily exposed to volatile hydrocarbons, especially those in marginal employment sectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The lung function tests results showed significantly lower MEF-50 and MEF-75 among petroleum refinery workers. Moitra et al, [ 23 ] reported that, subjects involved in manual cigarette lighter refilling with liquefied petroleum gas (LPG) have decrement in FEV1, FEV1/FVC Ratio. The adverse effect may be relevant to occupational group exposed to volatile hydrocarbons especially in employment sectors.…”
Section: Discussionmentioning
confidence: 99%
“…The lung function tests results showed significantly lower MEF-50 and MEF-75 among petroleum refinery workers. Moitra et al, [ 23 ] reported that, subjects involved in manual cigarette lighter refilling with liquefied petroleum gas (LPG) have decrement in FEV1, FEV1/FVC Ratio. The adverse effect may be relevant to occupational group exposed to volatile hydrocarbons especially in employment sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Although the translated version of this questionnaire has not been validated by formal assessment, we have employed this questionnaire in our previous studies [2426]. Subjective respiratory complaints in the previous 12 months included: 1) acute or chronic wheezing or whistling of the chest; 2) production of phlegm; 3) acute or chronic cough; 4) breathing trouble; 5) appearance of blood in sputum (haemoptysis); and 6) skin symptoms such as dryness, rash or irritation.…”
Section: Methodsmentioning
confidence: 99%
“…Respiratory symptoms were recorded using a previously used English-back Bengali-translated version of the European Community Respiratory Health Survey (ECRHS-II) questionnaire containing items on respiratory health, occupational exposure (in terms of total work experience in the sector) and lifestyle factors such as smoking habits (Moitra et al, 2013(Moitra et al, , 2014a(Moitra et al, , 2015b(Moitra et al, , 2016. Subjective respiratory complaints in the previous 12 months included: (a) acute/current or chronic/prolonged cough; (b) production of phlegm; (c) acute or chronic wheezing or whistling of the chest; and (d) breathing trouble.…”
Section: Respiratory Health Measuresmentioning
confidence: 99%